The Form of Love and Loyalty in the Animated Film â€œBilal: a New Breed of Heroâ€ By Ayman Jamal: The Perspective of Triangular of Love Theory of Robert J. Sternberg - izzah Himayatud Dauliyah; abdul basid (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2021)
Love and loyalty is one part of the package that helped stronger in some of relationship. What is love and loyalty in this research is not about love in the sense of romance between a man and a woman. Love and the loyalty which that will be studied in this research is about between families, friends, society, also between prophet and God. There for this research focuses on forms of love and loyalty beside of film "Bilal: a New Breed of Hero." This type of research is qualitative-descriptive. The primary data source used by researchers is film "Bilal: a New Breed of Hero" by Ayman Jamal airing in 2015 produced by Barajoun Entertainment Dubai. Theory that used was Triangular of Love perspective of Robert J. Sternberg's. Data collection techniques used are the technique of watching, listening and note taking. The data analysis technique that the researchers used was the Miles and Huberman model which consisted of data reduction, data presentation, and data verification. The result of this study shows that the forms of love and loyalty in the film "Bilal" consist of intimacy in the form of warmth, affection, calmness, also priority, etc; b) passion in the form of protecting, remembering, wanting to be together, helping, longing, submitting, and dominating; c) commitments in the form of sacrifice, loyalty, belief, trust, commitment and attention.